Reliability of power electronic converter systems - Chung, Henry Shu-hung; Wang, Huai; Blaabjerg, Frede; Pecht, Michael (London, United Kingdom The Institution of Engineering and Technology, 2015)
The book comprises of 16 chapters and covers the following aspects: power electronic converter systems; reliability engineering; power electronic packaging; wind turbine systems; power module; adjustable speed drive; and photovoltaic systems.
Electronic reproduction.
Keywords: Electric current converters; Electronic packaging; Photovoltaic power systems; Reliability; Variable speed drives; Wind turbines; Electronic books